Effectiveness of Video Observation of Procedural Skills in Surgical Performance of Ophthalmology Residents - Hussain Ahmad Khaqan, Usman Mahboob, Muhammad Ali Haider, Hasnain Muhammad Buksh, Hafiz Ateeq ur Rehman, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine effectiveness of video observation of procedural skills in surgical performance of ophthalmology residents. Methods: This experimental study was done at the department of Ophthalmology, Lahore General Hospital Lahore from 1st July to 31st Dec. 2018. Sample was collected using non-probability purposive sampling technique. One surgical procedure was done four times by each resident that included chalazion surgery, pterygium surgery, extracapsular cataract extraction and phacoemulsification surgery. Surgery of each resident was recorded; later procedural skills were assessed by two independent supervisors using Likert scale for each mini-skill. The difference in score of 1st VOPS till 4th VOPS of each resident was documented. Each procedure was evaluated through a validated proforma. Results: A total of twenty residents, five residents from each year of the four years residency program, age between 25 to 35 years, both gender male and female, who meet the inclusion criteria were included. Video observation of procedural skills (VOPS) scores of each resident demonstrated improved procedural skills in subsequent VOPS and mean scores of first VOPS versus fourth VOPS showed statistical improvement (p-value < 0.001). Mean VOPS score values of first year residents improved statistically from 6.60 ± 0.55 to 26.80 ± 1.10, for second year residents from 5.80 ± 0.84 to 22.60±1.82, similarly for third and fourth year residents mean VOPS score values also improved statistically from 12.00±1.87 to 41.60±3.29 and 17.20 ± 4.38 to 39.40 ± 4.28 respectively. Conclusion: Video Observation of Procedural Skills (VOPS) is effective in improving surgical skills of ophthalmology residents. Key words: Effectiveness, Ophthalmology Resident, Procedural Skills, Performance, Video Observation of Procedural Skills.